ζ ‘(0) の値

    \begin{align*} \zeta(s) &= \sum_{k=1}^\infty \frac{1}{k^s} \\ \eta(s) &= \sum_{k=1}^\infty \frac{(-1)^{k-1}}{k^s} \\ \end{align*}

とおく.

    \begin{align*} \eta(s) &= \sum_{k=1}^\infty \frac{(-1)^{k-1}}{k^s} \\ &= \frac{1}{2} \sum_{k=1}^\infty \left( \frac{(-1)^{k-1}}{k^s} + \frac{(-1)^{k-1}}{k^s} \right) \\ &= \frac{1}{2} + \frac{1}{2} \sum_{k=1}^\infty \left( \frac{(-1)^{k-1}}{k^s} + \frac{(-1)^{k}}{(k+1)^s} \right) \\ &= \frac{1}{2} + \frac{1}{2} \sum_{k=1}^\infty (-1)^{k-1} \left( \frac{1}{k^s} - \frac{1}{(k+1)^s} \right) \\ \end{align*}

これと, \eta(s) = (1 - 2^{1-s}) \zeta(s) であることより,

    \[\frac{1}{2} + \frac{1}{2} \sum_{k=1}^\infty (-1)^{k-1} \left( \frac{1}{k^s} - \frac{1}{(k+1)^s} \right) = (1 - 2^{1-s}) \zeta(s)\]

両辺を s について微分すると

    \begin{align*} \frac{d}{ds} (\text{LHS}) &= \frac{1}{2} \sum_{k=1}^\infty (-1)^{k-1} \left( \frac{- \log k}{k^s} - \frac{- \log (k+1)}{(k+1)^s} \right) \\ &= \frac{1}{2} \sum_{k=1}^\infty (-1)^{k} \left( \frac{\log k}{k^s} - \frac{\log (k+1)}{(k+1)^s} \right) \end{align*}

ここで, s = 0 のとき

    \begin{align*} \frac{1}{2} \sum_{k=1}^\infty (-1)^{k} \left( \log k - \log (k+1) \right) &= \frac{1}{2} \sum_{k=1}^\infty (-1)^{k} \log \left( \frac{k}{k+1} \right) \\ &= \frac{1}{2} \sum_{k=1}^\infty \left( - \log \left(\frac{k}{k+1}\right) + \log \left(\frac{k+1}{k+2}\right) \right) \\ &= \frac{1}{2} \sum_{k=1}^\infty \left( \log \frac{(k+1)^2}{k(k+2)} \right) \\ &= \frac{1}{2} \log \prod_{k=1}^\infty \left( \frac{(k+1)^2}{k(k+2)} \right) \\ &= \frac{1}{2} \log \left( \frac{\pi}{2} \right) \end{align*}

また,

    \begin{align*} \frac{d}{ds} (\text{RHS}) &= - (- \log 2) \cdot 2^{1-s} \cdot \zeta(s) + (1 - 2^{1-s}) \cdot \zeta '(s) \\ &= \log 2 \cdot 2^{1-s} \cdot \zeta(s) + (1 - 2^{1-s}) \cdot \zeta '(s) \end{align*}

ここで, s = 0 のとき

    \begin{align*} \log 2 \cdot 2 \cdot \zeta(0) + (1 - 2) \cdot \zeta '(0) &= \log 2 \cdot 2 \cdot \left( - \frac{1}{2} \right) - \cdot \zeta '(0) \\ &= - \log 2 - \cdot \zeta '(0) \end{align*}

以上より,

    \[\frac{1}{2} \log \left( \frac{\pi}{2} \right) = - \log 2 - \cdot \zeta '(0)\]

よって,

    \begin{align*} \zeta '(0) &= - \log 2 - \frac{1}{2} \log \left( \frac{\pi}{2} \right) \\ &= - \frac{1}{2} \left( 2 \log 2 + \log \left( \frac{\pi}{2} \right) \right) \\ &= - \frac{1}{2} \left( \log 4 + \log \left( \frac{\pi}{2} \right) \right) \\ &= - \frac{1}{2} \log \left( 4 \cdot \frac{\pi}{2} \right) \\ &= \boxed{- \frac{1}{2} \log (2 \pi)} \end{align*}